Multicentre observational study of the natural history of left-sided acute diverticulitis - Gian Andrea Binda; Alberto Arezzo; Alberto Serventi; L Bonelli (2011)
Abstract Background The natural history of acute diverticulitis (AD) is still unclear. This study investigated the recurrence rate, and the risks of emergency surgery, associated stoma and death following initial medical or surgical treatment of AD. Methods The Italian Study Group on Complicated Diverticulosis conducted a 4-year multicentre retrospective and prospective database analysis of patients admitted to hospital for medical or surgical treatment of AD and then followed for a minimum of 9 years. The persistence of symptoms, recurrent episodes of AD, new hospital admissions, medical or surgical treatment, and their outcome were recorded during follow-up. Results Of 1046 patients enrolled at 17 centres, 743 were eligible for the study (407 recruited retrospectively and 336 prospectively); 242 patients (32·6 per cent) underwent emergency surgery at accrual. After a mean follow-up of 10·7 years, rates of recurrence (17·2 versus 5·8 per cent; P < 0·001) and emergency surgery (6·9 versus 1·3 per cent; P = 0·021) were higher for medically treated patients than for those treated surgically. Among patients who had initial medical treatment, age less than 40 years and a history of at least three episodes of AD were associated with an increased risk of AD recurrence. There was no association between any of the investigated parameters and subsequent emergency surgery. The risk of stoma formation was below 1 per cent and disease-related mortality was zero in this group. The disease-related mortality rate was 0·6 per cent among patients who had surgical treatment. Conclusion Long-term risks of recurrent AD or emergency surgery were limited and colectomy did not fully protect against recurrence.